Penerapan Media Gamifikasi untuk Meningkatkan Pengetahuan Mahasiswa Keperawatan pada Pembelajaran Sistem Pernapasan - Fransiska Kurniati Natul; Lidwina Dewiyanti Wea; Maria Getrida Simon; Yohana Hepilita (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the effect of gamification media on nursing students' knowledge in the respiratory pathophysiology course in the Nursing Study Program, St. Paul Catholic University of Indonesia, Ruteng. The method used was quantitative with a pre-experimental design using a One Group Pretest-Posttest Design. The results showed a p-value of 0.000 (<0.05), indicating that gamification media had an effect on students' knowledge. The results showed a difference in knowledge before and after the gamification method was implemented in respiratory system learning. In conclusion, this method was superior to conventional methods. In conclusion, gamification methodology has proven effective in increasing knowledge levels and should be used consistently in learning. Keywords: Nursing Gamification, Method, Learning, Knowledge